Czy systemowość jest konieczną właściwością prawa? - Dyrda, Adam; Gizbert-Studnicki, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This question is a metaphysical question, as it relates to the nature of law. The answer must be based on the conceptual analysis. The method of conceptual analysis applied by contemporary analytic theories of law may be interpreted as a „modest” conceptual analysis in the terminology of F. Jackson. The basis of such an analysis are platitudes about law, generally accepted in a given society and the purpose of analysis is the rational reconstruction of the folk theory of law. Using this method, the authors come to the conclusion that necessarily any rationally reconstructed folk theory of law must contain the claim that the law constitutes a system, at least in the weak sense of the word.
Keywords: teoria prawa; natura prawa; Hart, Herbert L.A. (1907-1992); Jackson, Frank